2014
DOI: 10.5713/ajas.2014.14016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Relationships of Korean Chicken Breeds Based on 30 Microsatellite Markers

Abstract: The effective management of endangered animal genetic resources is one of the most important concerns of modern breeding. Evaluation of genetic diversity and relationship of local breeds is an important factor towards the identification of unique and valuable genetic resources. This study aimed to analyze the genetic diversity and population structure of six Korean native chicken breeds (n = 300), which were compared with three imported breeds in Korea (n = 150). For the analysis of genetic diversity, 30 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
12
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
5
12
1
5
Order By: Relevance
“…These results are similar to those reported in different chicken populations by Davila et al (2009), and Abebe et al (2015). However, Hillel et al (2003) and Suh et al (2014) reported higher values for mean allele numbers per locus. The number of alleles observed across the loci is greater than the effective number of alleles, which is as expected and also as reported by Liu et al (2008).…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to those reported in different chicken populations by Davila et al (2009), and Abebe et al (2015). However, Hillel et al (2003) and Suh et al (2014) reported higher values for mean allele numbers per locus. The number of alleles observed across the loci is greater than the effective number of alleles, which is as expected and also as reported by Liu et al (2008).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the demand for Korean native chicken breeds (KNCBs) increased suddenly as they suit the Korean palate and as the National institute of Animal Science (Korea) realized the necessity of conserving native breeds [ 5 ]. Thus, semen quality checking is required for successful semen conservation and AI.…”
Section: Introductionmentioning
confidence: 99%
“…현재까지 오계를 포함하여 우리나라의 재래닭 및 외래토착 종을 대상으로 MS 마커를 이용한 연구가 다수 보고되어 왔 으며, 오계 집단은 재래닭 및 외래토착종 집단과는 다른 하 나의 순수한 집단으로 뚜렷하게 구분되는 것으로 나타났다 (Lee et al, 2010;Suh et al, 2014;Seo et al, 2015 (Kong et al, 2006;Seo et al, 2013;Suh et al, 2014)에서도 높은 다형성을 나타내고 있는 것으로 보고되었다.…”
unclassified